Structure of subjective social well-being of personality - T. Danilchenko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
Article is devoted illumination of approaches (sociological and psychological) to definition of structure of subjective social well-being. Author proposes his own position about key elements of their phenomena.